Steve Reich: a bio-bibliography - Hoek, D. J. (Westport, Connecticut - London Greenwood press, 2001)
In the late 1960s and early 1970s, Steve Reich was considered a fringe experimentalist. His work consisted largely of repeating, slowly changing patterns unlike either the serialism or the aleatory that predominated at that time. Today, however, Reich is one of the most prominent and celebrated contemporary composers, one about whom the scholarly and popular literature offers an assortment of critical, historical, and analytical perspectives. Author D.J. Hoek's bio-bibliography serves as an essential guide to this literature, comprehensively surveying Reich's life and work.Included are details of all of Reich's compositions: dates, instrumentation, premiere performances, and publishers; a discography listing all commercial recordings of the composer's oeuvre; and an annotated bibliography of publications in English, French, German, and Italian. The Reich scholar or aficionado could not find a more thorough encapsulation of his brilliant career.